STRATEGI PENERAPAN KEMAMPUAN KOLABORASI SISWA SEKOLAH DASAR PADA PEMBELAJARAN BAHASA INDONESIA MELALUI MODEL THINK TALK WRITE (TTW) - Ariestiyani, Ema; Rachmadtullah, Reza (Universitas Negeri Medan, 2025)
21st century learning emphasizes four key skills, including collaboration. Students' limited ability to collaborate in learning, particularly in Indonesian language subjects, is influenced by the use of conventional teaching methods. The aim of this research is to investigate the influence of the Think Talk Write (TTW) learning approach on enhancing the cooperative abilities of elementary school pupils in Indonesia. This study is a quantitative research with the Quasi-Experimental method and uses Post-Test Only Control Group Design as a design. This research was carried out at SDN Keboananom Gedangan. The study involved two classes: Class III A (experimental) and Class III B (control). The process of gathering data was conducted using questionnaires. The collected data was analyzed with the SPSS software program version 21. Referring to the results of data analysis, it can be concluded that the Think Talk Write (TTW) learning strategy has a significant impact on the collaborative ability of Elementary School students in Indonesian subjects. The existence of this research intends to offer accurate knowledge, insights, and information to readers in the future.